Inhibition of Plasmodium falciparum Lysyl‐tRNA Synthetase via a Piperidine‐Ring Scaffold Inspired Cladosporin Analogues. (28th May 2021) - Babbar, Palak; Sato, Mizuki; Manickam, Yogavel; Mishra, Siddhartha; Harlos, Karl; Gupta, Swati; Parvez, Suhel; Kikuchi, Haruhisa; Sharma, Amit
Abstract: Plasmodium falciparum lysyl‐tRNA synthetase ( Pf KRS) represents a promising therapeutic anti‐malarial target. Cladosporin was identified as a selective and potent Pf KRS inhibitor but lacks metabolic stability. Here, we report chemical synthesis, biological evaluation and structural characterization of analogues where the tetrahydropyran (THP) frame of cladosporin is replaced with the piperidine ring bearing functional group variations. Thermal binding, enzymatic, kinetic and parasitic assays complemented with X‐ray crystallography reveal compounds that are moderate in potency. Co‐crystals of Cla−B and Cla−C with Pf KRS reveal key atomic configurations that allow drug binding to and inhibition of the enzyme. Collectively these piperidine ring scaffold inhibitors lay a framework for further structural editing and functional modifications of the cladosporin scaffold to obtain a potent lead. Abstract : This study focuses on the synthesis and structural analysis of piperidine ring inspired cladosporin inhibitors against Plasmodium falciparum lysyl‐tRNA synthetase ( Pf KRS). The series retains selectivity against its human counterpart but it was observed that replacing the tetrahydropyran moiety by piperidine reduces potency. Co‐crystals of Cla−B and Cla−C with Pf KRS reveal key interactions and loop readjustments that allow drug binding and inhibition of the enzyme.